Childhood lead exposure, childhood trauma, substance use and subclinical psychotic experiences–a longitudinal cohort study. (30th May 2016) - Galletly, Cherrie; Clark, Levina; McFarlane, Alexander; Searle, Amelia; Sawyer, Michael; Sim, Malcolm; Baghurst, Peter; van Hooff, Miranda
Abstract: This study examined the long-term associations between childhood lead exposure, childhood trauma and adult substance use, and subclinical psychotic experiences (SPEs) in the Port Pirie Cohort Study. Adult participants were initially 402 (175 males, 227 females) 25–29 year-olds followed up from the Port Pirie Cohort Study that commenced in 1979 (55.6% of the original cohort). Multiple linear regression analyses were conducted on a sub-sample of 158 participants for which adequate data was available. Variables examined as correlates of positive, negative and depressive SPEs included socioeconomic status at birth, cumulative blood lead level at age 7, maternal mental health, family functioning and cognitive ability at age 11-13, and adverse childhood experiences, alcohol use and cannabis use assessed during adulthood. Cumulative blood lead levels at age 7 were bi-variately associated with the frequency of positive SPEs in adulthood; however this relationship was not significant when other variables were accounted for. Adverse childhood experiences and substance use (cannabis use in particular) were significant correlates of SPEs in adulthood. Highlights: The Port Pirie Cohort study examined individual and environmental factors related to subclinical psychotic experiences (SPEs) during adulthood. The bi-variate relationship between cumulative blood lead levels at age 7 and positive SPE frequency in adulthood in females was no longer significant when other variables were accounted for. Adverse childhood experiences and substance use (cannabis use in particular) were associated with SPEs in adulthood.